Effect of nitrogen and zinc application on growth, grain quality and nutrient indices of direct seeded rice (Oryza sativa L) - Rajendra Prasad Meena; S.K. Prasad; M.K. Singh (Annals of Agricultural Research, 2023)
A field experiment was conducted during the rainy (kharif) season of 2014 - at Varanasi, Uttar Pradesh, to study the effect of nitrogen (N) and zinc (Zn) application on yield and zinc content in directseeded rice (DSR). The experiment was laid out in factorial randomized block design with replication thrice. The treatments included 4 N rates (0, 90, 120 and 150 kg/ha) and 4 Zn application (0 kg ZnSO4 .H2 O, 0.3% ZnSO4 .H2 O spray at anthesis, 0.3% ZnSO4 .H2 O spray at early milk, 0.3% ZnSO4 .H2 O spray at dough stage). The highest growth attributes (plant height, tillers/running meter, fresh weight, dry weight and RGR), grain yield and agronomic indices of N and Zn in DSR were recorded with application of 150 kg N/ha, However among zinc scheduling 0.3% ZnSO4 .H2 O spray at anthesis led the highest value of all the growth attributes. For grain quality, the combination of 150 kg N/ha and 0.3% ZnSO4 .H2 O spray at dough resulted in the maximum grain protein content and protein yield.